Evaluating the Correlation between Brain Ultra Sonographic, Brain MRI, and Electroencephalography Findings and the Severity of Asphyxia and Neurodevelopment in Infants with Hypoxic-ischemic Injury - Enhesari, Ahmad; Nejad Biglari, Habibe; Shafie’ei, Mohammad; Sirooee Nejad, Mahsa; Daei Parizi, Zahra; Eftekhar Vaghefi, Rana (Iranian Journal of Child Neurology, 2022)
Objective Hypoxia-ischemia-induced brain injury is a major cause of acute mortality and chronic neurological disability in infants and children. Imaging plays a vital role in diagnosing and treating hypoxicischemic encephalopathy (HIE) and as an adjunct to acute conditions and provides valuable information on long-term prognosis. Materials & Methods Our study was prospective with 50 neonates aged 34 weeks and older with HIE. Cerebral ultrasound and MRI were performed on the infants, and the pattern of lesions was recorded. A pediatric neurologist examined the infants, and their developmental status was assessed and recorded with electroencephalography (EEG) findings. The data were analyzed. Results The sonography pattern was normal in 26 (76.5%) term neonates, and also, the PVL pattern was observed in 10 term neonates. The incidence of observing an edema pattern (17.6%) was significantly different between the term and pre-term infants (P-value = 0.001). MRI findings were normal in 20 (58.8%) term neonates and 11 premature neonates. However, the PVL pattern was observed in MRI performed in six term neonates (6.6%). The watershed pattern (17%) showed that these differences were significant between the term and pre-term infants (P-value = 0/001). Conclusion Normal sonography was significantly higher in neonates with normal neurodevelopment than in patients with normal MRI and EEG findings but with poor neurodevelopment. Also, the probability of having normal MRI results was lower in neonates with moderate to severe asphyxia compared to ultrasound and EEG.